KORELASI KADAR LEUKOSIT SEBAGAI PREDIKTOR PERFORASI APENDIKS PADA APENDISITIS AKUT - Silaban, Irene; Butar-butar, Harry; Silitonga, Hendrika A. (Jurnal Kedokteran Methodist, 2020)
Background : Appendicitis is inflammation that occurs in the appendix vermiformis. Appendicitis is the most common cause of acute abdominal pain which requires immediate surgery to prevent appendix perforation. Examination of leukocyte levels is one of the parameters for the diagnosis of appendicitis. However, it is not clear the difference in leukocyte levels between acute appendicitis and perforated appendicitis. The purpose of this study was to determine the correlation between leucocyte levels as a predictor of appendix perforation in acute appendicitis. Method : The research method used was a Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were 5 journals with inclusion criteria for the publication date of the last 10 years, the language used was Indonesian or English, with the subject of the study of patients with a diagnosis of acute appendicitis, perforated appendicitis and full text publication. Conclusion : Leukocyte levels can be used as a supporting diagnosis to distinguish acute appendicitis from perforated appendicitis, where the leucocyte level in perforated appendicitis is higher than in acute appendicitis.